2016
DOI: 10.1177/1087054716659362
|View full text |Cite
|
Sign up to set email alerts
|

Females With ADHD Report More Severe Symptoms Than Males on the Adult ADHD Self-Report Scale

Abstract: The results suggest that childhood symptoms of ADHD may have gone unnoticed in girls, emphasizing the need for longitudinal studies of ADHD symptoms across the life span.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 37 publications
(42 reference statements)
11
20
1
Order By: Relevance
“…The total ASRS‐v1.1 Symptom Checklist score estimated in this study suggests that the overall level of ADHD symptoms in the US general adult population (most of whom do not have ADHD) is quite low. Results were consistent with prior research that showed higher ADHD symptom severity among younger and female adults . The normative data generated for the ASRS‐v1.1 Symptom Checklist in this study can be used to assess the deviance of individual scores in clinical settings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The total ASRS‐v1.1 Symptom Checklist score estimated in this study suggests that the overall level of ADHD symptoms in the US general adult population (most of whom do not have ADHD) is quite low. Results were consistent with prior research that showed higher ADHD symptom severity among younger and female adults . The normative data generated for the ASRS‐v1.1 Symptom Checklist in this study can be used to assess the deviance of individual scores in clinical settings.…”
Section: Discussionsupporting
confidence: 88%
“…Results were consistent with prior research that showed higher ADHD symptom severity among younger and female adults. 15,16 The normative data generated for the ASRS-v1.1 Symptom Checklist in this study can be used to assess the deviance of individual scores in clinical settings. By placing scores in the appropriate demographic context, the results of this study help guide clinicians in understanding a patient's symptom profile and symptom burden, based on his/her ASRS-v1.1 Symptom Checklist score.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have failed to show these gender differences in psychiatric comorbidities, and none have evaluated interactions on an additive scale. Women with ADHD have been shown to report more symptoms and impairments resulting from their condition than men, thus possibly predisposing them to a higher level of psychiatric comorbidity . Our results show that there is a relatively higher increase in prevalence of most psychiatric comorbidities associated with ADHD in women with ADHD fitting this.…”
Section: Discussionsupporting
confidence: 46%
“…It is also known that women with ADHD are more frequently diagnosed with the inattentive subtype, as defined in DSM‐IV/DSM‐5 , with more internalizing comorbid disorders such as depression and anxiety. Women also report more impairment than men , and a study based on self‐reports among adults showed that women with ADHD, more often than men, reported a history of treatment for other psychiatric disorders than ADHD . The combined subtype, with more externalizing symptoms, is more frequent in men .…”
Section: Introductionmentioning
confidence: 99%
“…The higher prevalence rates of AUD and DUD in men compared to women are in accordance with gender differences in the general population (34,35,36,37). In line with others we find that women reported higher levels of hyperactivity-impulsivity (46) and ED (47) compared with men. This is still consistent with our findings that hyperactivity-impulsivity and ED in both women and men are associated with DUD.…”
Section: Discussionsupporting
confidence: 93%